Numerical Simulation of Acoustic Emission Events in Supporting Roadways under Different Dynamic Loads - Wenzheng Shang; Zhigang Liu; Jianbo Yuan; Wuchao You; Shuai Han; Lei Yu; Shihua Zhang (Advances in Materials Science and Engineering)
This paper studies the distribution characteristics of acoustic emission (AE) events in supporting roadways under different dynamic load conditions through numerical simulation and theoretical analysis. According to the principle of AE numerical simulation, the roadway model is established by FLAC3D software, and the supporting structure of the bolt cable is established by editing the Fish function. According to the model dynamic load application criterion, the relationship between the peak velocity of the particle, the distance from the source center to the dynamic impact damage point, and the dynamic load intensity is introduced. The velocity-distance-energy relationship is deduced from the relationship to determine the magnitude of the dynamic load energy. The simulation results show that the intensity of the dynamic load source and the distance of the dynamic load source directly impact the AE events. The larger the dynamic load intensity and the closer to the dynamic load source, the more concentrated the AE events. The roadway has a blocking effect on the transmission of the dynamic load stress waves. According to this characteristic, the roadway can be protected by a high-pressure relief roadway. Rock lithology greatly influences the transmission of dynamic load stress waves and the number of AE events. When the dynamic load stress wave passes through the rock strata of different lithologies, the attenuation of the dynamic load energy and the number of AE events are large. However, when the dynamic load stress wave passes through the rock strata of the same lithology, the attenuation of the dynamic load energy and AE events is small. The surrounding rock structure in the bottom corner area of the roadway is susceptible to disturbance from dynamic load sources above the roadway. The results are greatly significant for studying the AE characteristics of support roadways with disturbance-typeimpact failure.